Analisis Perbedaan Hak Konsumen atas Produk dan Layanan Berkualitas antara Konsumen Online dan Konsumen Swalayan - Hilda Damara; Intan Putri Munggaran; Naysilla Aditiya Salma (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
Shopping in the modern era has become very diverse. Based on the method of shopping, it can be divided into two categories:online shopping and self-service shopping. As consumers, we also needprotection, whether we are online consumers or self-service consumers. Consumerprotection is established to ensure that the rights of consumers are recognized,respected, and protected by businesses, the government, and other institutions. In the differences in consumer rights between online and supermarket consumers regarding quality products and services,it is equally important to enhance these rights to ensure mutual comfort.This study aims to identify and analyze the differences in consumer rightsbetween online consumers and retail consumers regarding quality products and services. The data analysis technique used is qualitative analysis by collecting consumer opinions using Google Forms. The results of this study and discussion highlight the differences in consumer rights regarding quality products and services between online consumers and retail consumers, while upholding consumer rights in accordance with Law No. 8 of 1999 on Consumer Protection, Article 4 of the Consumer Protection Law, Article 62(1) of the Consumer Protection Law, and the Civil Code regarding sales contracts, hidden defects in goods, and liability for compensation.